IFRS Implementation in Management Accounting Systems: A Systematic Review on Financial Reporting Quality - Ita Salsalina Lingga; Yassine Oubahou; Khalid El Ouafa (Generate Digital Publishing, 2025)
Objective: This study examines the implementation of International Financial Reporting Standards (IFRS) and its impact on the quality of financial reporting, with an emphasis on the role of management accounting systems (MAS).Research Design & Methods: This study uses a systematic literature review (SLR) approach, analyzing various findings from articles indexed in Scopus (Q1–Q4) with the basic keywords IFRS, quality of financial statements, and management accounting system, focusing on quantitative and qualitative findings related to the adoption of IFRS.Findings: The results show that IFRS adoption generally improves accounting quality by reducing earnings management, increasing loss recognition, and strengthening investor confidence. However, the effectiveness of IFRS remains limited in countries with weak law enforcement and low institutional readiness. Evidence from Russia and Ukraine shows that partial implementation limits the expected benefits, while Germany's two-tier enforcement system effectively detects but fails to prevent future reporting irregularitiesImplications & Recommendations: Organizations need to strengthen internal controls, audit mechanisms, and management accounting systems to ensure that the adoption of IFRS results in substantial quality improvements. Policymakers need to provide regulatory clarity, capacity building, and encourage digital innovation to support accurate reporting.Contribution & Value Added: This study provides cross-country insights into how IFRS interacts with management accounting practices, emphasizing that the success of IFRS depends on institutional capacity, governance quality, and technology integration.